Sistema de coordenação de ordens de produção baseado na estratégia bata de manufatura - Bianco, Vinícius Soares Del (2008)
This work presents a proposal of implementing an Ordering System based on the Bata Manufacturing Strategy (BMS). The aim is to verify the interference and effectiveness of this system on the activities of the Production Planning and Control of a thermoplastics process factory. Its theory s reference comes from the Bata Manufacturing Strategy (BMS), the Ordering Systems (OS) and the Performance Measurement Systems (PMS). The Action- Research method was used to verify the relation between the ideal model and the one obtained when put on a practical experience. Firstly, a model system is proposed on what this work was developed, its main features and details that connect the BSM, the OS and the PMS. Then, an application example of the system in a thermoplastics process factory is showed using the blow molding process of High Density Polyethylene and Polyvinyl Chloride bottles for cosmetics industries and drugstores. Furthermore, the main results obtained when implementing this system are also presented as well as an evaluation of the procedures created to control the material and human resources and how these controls influence the Production Planning and Control activities of this factory. Another important point of this work is also to present a new approach on how to implement the Bata Manufacturing Strategy